APPENDIX 3B Trypan Blue Exclusion Test of Cell Viability. (2nd November 2015) - Strober, Warren
Abstract : The protocol described in this appendix allows for light microscopic quantitation of cell viability. Cells are suspended in PBS containing trypan blue and then examined to determine the percentage of cells that have clear cytoplasm (viable cells) versus cells that have blue cytoplasm (nonviable cells). © 2015 by John Wiley & Sons, Inc.